Improved Calibration and Data Processing Procedures of OPUS Optical Sensor for High-Resolution in situ Monitoring of Nitrate in Seawater - Nehir, Münevver; Esposito, Mario; Begler, Christian; Frank, Carsten; Zielinski, Oliver; Achterberg, Eric P. (Frontiers in Marine Science, 2021)
Nitrate, an essential nutrient for primary production in natural waters, is optically detectable in the ultraviolet spectral region of 217–240 nm, with no chemical reagents required. Optical nitrate sensors allow monitoring at high temporal and spatial resolutions that are difficult to achieve with traditional approaches involving collection of discrete water samples followed by wet-chemical laboratory analysis. The optical nitrate measurements are however subject to matrix interferences in seawater, including bromide, at the spectral range of interest. Significant progress has been made over the last 10 years in improving data quality for seawater nitrate analysis using the ISUS and SUNA (Seabird Scientific, United States) optical sensors. Standardization of sensor calibration and data processing procedures are important for ensuring comparability of marine nitrate data reported in different studies. Here, we improved the calibration and data processing of the OPUS sensor (TriOS GmbH, Germany), and tested five OPUS sensors simultaneously deployed under identical conditions in the laboratory in terms of inter-sensor similarities and differences. We also improved the sampling interval of the OPUS to 3 s in a continuous mode by a custom-built controller, which facilitates the integration of the sensor into autonomous profiling systems. Real-time, high-resolution, in situ measurements were conducted through (1) underway surface measurements in the southeastern North Sea and (2) depth profiles on a conductivity–temperature–depth frame in the tropical Atlantic Ocean. The nitrate data computed from the optical measurements of the sensor agreed with data from discrete water samples analyzed via conventional wet-chemical methods. This work demonstrates that the OPUS sensor, with improved calibration and data processing procedures, allows in situ quantification of nitrate concentrations in dynamic coastal waters and the open ocean, with an accuracy better than ∼2 μM and short-term precision of 0.4 μM NO3–. The OPUS has a unique depth rating of 6,000 m and is a good and cost-effective nitrate sensor for the research community.